2020
DOI: 10.3390/polym12030504
|View full text |Cite
|
Sign up to set email alerts
|

Fluorination Effect for Highly Conjugated Alternating Copolymers Involving Thienylenevinylene-Thiophene-Flanked Benzodithiophene and Benzothiadiazole Subunits in Photovoltaic Application

Abstract: Two two-dimensional (2D) donor–acceptor (D-A) type conjugated polymers (CPs), namely, PBDT-TVT-BT and PBDT-TVT-FBT, in which two ((E)-(4,5-didecylthien-2-yl)vinyl)- 5-thien-2-yl (TVT) side chains were introduced into 4,8-position of benzo[1,2-b:4,5-bʹ]dithiophene (BDT) to synthesize the highly conjugated electron-donating building block BDT-TVT, and benzothiadiazole (BT) and/or 5,6-difluoro-BT as electron-accepting unit, were designed to systematically ascertain the impact of fluorination on thermal stability,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 100 publications
(168 reference statements)
0
5
0
Order By: Relevance
“…Finally, E13 :PC 71 BM-based devices exhibited a slightly higher PCE of 5.22% than E12 (4.50%) as a result of the deepened HOMO level, increased charge mobility, and better microstructural morphology. 71 Meanwhile, it is easy to see that TT is better than BT in this category of polymers.…”
Section: Tvt -Based P-type Materialsmentioning
confidence: 99%
“…Finally, E13 :PC 71 BM-based devices exhibited a slightly higher PCE of 5.22% than E12 (4.50%) as a result of the deepened HOMO level, increased charge mobility, and better microstructural morphology. 71 Meanwhile, it is easy to see that TT is better than BT in this category of polymers.…”
Section: Tvt -Based P-type Materialsmentioning
confidence: 99%
“…The D1 unit has a large planar conjugate structure, forming π-π stacking, which may result in high hole mobility and charge carrier transport rate [ 30 , 31 , 32 ]. At present, conjugated polymers based on benzodithiophene are mainly used in the construction of organic photovoltaic (OPV) [ 33 , 34 ], and there are relatively few reports on electrochromic properties [ 35 ]. In order to improve the solubility of polymer and achieve large-scale production and application of electrochromic materials, it is a useful and common method to incorporate long alkyl or alkoxy side chains into the backbone of the polymer molecular framework structure.…”
Section: Introductionmentioning
confidence: 99%
“…There is a vast array of diverse organic dye groups, and their base continues to expand, which is positive and desirable in the context of unlocking their potential. Continuously updating known dyes with specific functional groups is highly valuable, as it leads to the discovery of their new capabilities and possibilities. Within the framework of these considerations, benzothiadiazole derivatives have garnered significant attention in the field of optoelectronics due to their unique properties and potential applications. These materials are the integral components of various organic semiconductors and conjugated polymers utilized in photonic devices. , Their molecular structure facilitates efficient charge transport and excellent electron-accepting capabilities, making them suitable candidates for use in organic photovoltaic cells and light-emitting diodes (LEDs). The presence of electron-withdrawing moieties in the benzothiadiazole scaffold enhances the intramolecular charge transfer, leading to improved photoconversion efficiency in photovoltaics. Furthermore, the π-conjugation within benzothiadiazole derivatives contributes to their remarkable light-absorbing properties, enabling them to effectively harvest solar radiation across a broad spectrum. The systematic tuning of their electronic and optical properties through chemical modifications enables the design of tailored materials for specific optoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the structural versatility of benzothiadiazole derivatives allows for facile incorporation into various device architectures, promoting their compatibility with flexible and lightweight optoelectronic platforms. 35 In this study, we present the random lasing (RL) phenomenon observed for the first time in the 4,7di(thiophen-2-yl)benzo[c] [1,2,5]thiadiazole (abbreviated here as DTBT) compound. 38−41 The mechanism relies on the constructive scattering of light within a disordered medium.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation